Detection of the knee point in lithium-ion battery degradation using a state-of-charge-dependent parameter - Hyunjae Kim; Inwoo Kim; Minsoo Kim; Seongha An; Hyo Chul Ahn; Dongmin Park; Jun Hee Lee; Chun Yong Kang; Jang Wook Choi (Proceedings of the National Academy of Sciences, 2025)
The rapidly expanding lithium-ion battery (LIB) market has heightened the demand for efficient diagnostics for in-use cells and the reliable grading of used cells. Various purpose-built analysis tools and statistical algorithms have been developed, but often rely on redundant instrumentation and computationally intensive procedures. Here, we propose using the variance of the capacity difference between 0.2C and 1C, Var(Δ Q 0.2C-1C (V) ), based on the strong correlation between the interfacial state of the anode and mode of capacity degradation, as a measure of the health state of individual cells. A single-point “off-board” measurement of Var(Δ Q 0.2C-1C (V) ) indicates whether a particular cell is experiencing self-limiting or accelerating degradation and is thus near a knee point in its cycle life. This assessment additionally provides a quantitative criterion for differentiating used cells for reuse or recycling. Our findings suggest that utilizing state-of-charge-dependent key electrochemical properties enables the cell health to be accurately monitored, thereby promoting sustainability in the expanding battery market.